ANALISIS PERPUTARAN ASET, PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSETS - Puspitasari, Ratih; Sahala, Bintang; Cecilia, Cecilia (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The purpose of this study was to determine and analyse whether or not the relationship between asset turnover and return on assets of a company, to analyze whether there is any relationship working capital turnover and return on assets of a company, and to analyze a relationship between asset turnover, working capital turnover against return on assets of a company. The research conducted by the author at. Indofood Sukses Malanur Tbk, PT. Mayora Indah Tbk, PT. Ultrajaya Milk Industry & Trading Company. The result showed the tumover of assets as measured by TATO, working capital tumover, as measured by NWCTO, the return on assets measured by ROA at. Indofood Sukses Malanur has a positive effect and no significant between asset turnover, working capital turnover on return on assets. PT.Mayora Indah Tbk obtained results asset tumover (TATO) had no significant positive effect on retum on assets andfor working capital turnover (NWCTO) has a negative and no significant effect. While at PT. Ultrajaya Milk Industry & Trading company obtained the result that the asset turnover (TATO) has a positive and significant effect on return on assets and for working capital turnover (NWCTO) has a negative and no significant effect on PT. Ultrajaya Milk Industry & Trading Company Tbk Keywords: Asset Turnover, Working Capital Turnover, Return on Assets